Cattle grazing effects on annual plants assemblages in the Central Monte Desert, Argentina - Sassi, Paola Lorena (2009)
Plant assemblages' dynamics have been studied to evaluate the influence of different environmental factors. The aim of our work was to assess the effect of a disturbance in the form of livestock grazing on annual plants, in a South American desert. We tested the exclusion of cattle grazing by comparing the composition of annual plants in three major vegetation types within a MaB Reserve in the Monte Desert of Argentina, with those of an adjacent grazed field. Sampling was conducted in two consecutive years that differed in precipitation. We established three sampling sites within each vegetation type at the reserve and the grazed field. Transects were set to assess plant cover, abundance, and richness. Theoretically, changes in diversity are explained by changes in one of its components: species richness. Species richness of annual plants was not different between the grazed and ungrazed sites. However, plant cover and diversity were lower in grazed sites, whereas abundance increased. Owing to a strong species-specific effect, we propose that it is evenness the main parameter involved in diversity dynamics in the heterogeneous vegetation mosaic of the Monte desert. Finally, vegetation types (spatial heterogeneity) and rainfall regime (temporal heterogeneity) greatly interacted with grazing effects. We endorse the idea that rapid responses of annual plant assemblages to changes in rainfall conditions coupled with herbivore control, might result in a restoration pathway for degraded arid landscapes.